CORRELATION BETWEEN VISUAL CHARACTERS AND SENSE OF PLACE IN KAMPUNG PELANGI SEMARANG - Yumnahanin, Wulasty Digda; Rukayah, Siti (Journal of Architecture&ENVIRONMENT, 2023)
Kampung Pelangi Semarang is in Randusari Village, South Semarang District, Semarang City. Kampung Pelangi, formerly known as Kampung Wonosari, was a slum village, through the Semarang City Government program it has become a thematic tourist village, as an effort to improve the arrangement and increase the economic potential of Kampung Pelangi. After experiencing a change in visual character, the actions of the residents show a change in the sense of place of Kampung Pelangi. This action is reflected in changes in the sense of pride, ownership, identity, positive aspirations, and commitment of residents to Kampung Pelangi. The purpose of this study was to determine the relationship between visual characters and the sense of place in Kampung Pelangi. This research method is quantitative. Data collection using a questionnaire. The research sample is 100 residents of Pelangi village aged 25-60 years. The data analysis method used is correlation inferential statistical analysis using the IBM SPSS Statistics 26 for windows program. The results of this study found that the relationship between visual characters and the sense of place in Kampung Pelangi was positive, so that the more visual characters increased, the sense of place in Kampung Pelangi also increased.